New Concepts of Antiviral Therapy - Bogner, Elke.; Holzenburg, Andreas; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2006)
Antiviral drugs are important tools for treatment or prevention of viral infections. These drugs were first used for monotherapy, but nowadays combinations of antiviral agents are often part of a standard treatment as evidenced by e.g. HAART (highly active antiretroviral therapy). However, in almost every case of antiviral therapy, drug resistant viruses appear. In addition, the low oral bioavailability, toxicity and the number of severe side effects still pose significant problems. All of the latter issues limit the clinical usefulness and drive the need for improved antiviral strategies. These strategies include new drugs and targets, novel modes of action, vector-based treatments and even the block of defined genes by inhibiting mRNA formation (siRNA). Highlights of this book include the discussion of: - novel, promising compounds - concepts of therapy for new/emerging viruses - managing drug resistance - new therapeutic strategies This book presents an overview of the most recent developments. Contributions were carefully selected to ensure quality coverage by acknowledged experts over a wide spectrum and should prove to be of great value to students and serve as a compendium for R and D and educational professionals.
Concepts of therapy for RNA viruses -- Therapeutic vaccination in chronic hepadnavirus infection -- Characterization of targets for antiviral therapy of Flaviviridae infections -- Inhibition of Hepatitis C virus by nucleic acid-based antiviral approaches -- Inhibitors of respiratory viruses -- Anti-viral approaches against influenza viruses -- A new approach to an Influenza virus live vaccine: Modification of eleavage site of the haemagglu reverse genetics -- New concepts in anti-HIV therapies -- Evaluation of current strategies to inhibit HIV entry, integration and maturation -- Managing antiretroviral resistance -- Concepts of therapy for DNA viruses -- Selective inhibitors of the replication of poxviruses -- Maribavir: A promising new antiherpes therapeutic agent -- Benzimidazole-D-ribonucleosides as antiviral agents that target HCMV terminase -- Recent developments in anti-herpesviral therapy based on protein kinase inhibitors -- Immune therapy against papillomavirus-related tumors in humans -- Concepts of therapy for emerging viruses -- The SARS Coronavirus receptor ACE 2 A potential target for antiviral therapy -- Therapy of Ebola and Marburg virus infections -- General concepts of therapy -- Proteasome inhibitors as complementary or alternative antiviral therapeutics -- Human monoclonal antibodies for prophylaxis and therapy of viral infections -- Vector-based antiviral therapy.
Keywords: Virology; Medical microbiology; Pharmacology; Microbiology; Medical biochemistry; Virology; Medical Microbiology; Pharmacology/Toxicology.; Microbiology; Medical Biochemistry